Phūminām : khwāmpenmā læ khwāmmāi kh̨ōng ch̄ư bān nai khēt ʻAmph̄œ Bān Ph̄ư, ʻUd̨ōn Thānī - ʻArunsak Kingmanī (ʻUtthayān Prawattisāt Phū Phrabāt ; Samnakngān Bōrānnakhadī læ Phiphitthaphanthasathān h̄æng Chāt thī 7 Kh̨̄on K̄æn, 2000)
On the history of the geographic names of Amphoe Ban Phu, Udon Thani Province, Northeast Thailand.